Case Reviews: Vedanta, a Long Awaited Landmark in Extraterritorial Tort Litigation against Parent Companies: Reflections on 'Vedanta's' Supreme Court Decision on Jurisdiction. (April 2019) - Blanco, Elena
No abstract available